1945
DOI: 10.2307/626338
|View full text |Cite
|
Sign up to set email alerts
|

Vases from Odos Pandrosou

Abstract: The showcases of the antique-dealers in Odos Pandrosou are full of little lekythoi which were painted for the tombs of humble men of the people, and which to-day are destined for modest purchasers or for the Inspectors of the Archaeological Section of the Ministry of Education, while for more important purchasers there are hidden away somewhere else works of much greater value. It is seldom that we are stopped by the art or the subject of one of these lekythoi.In 1943 when I was making an inventory of the stoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Bulle (1937) thinks the performance was a private one for an aristocratic erastes and his young eromenos . Karouzou (1945) takes the absence of a mask to mean that the spectators were a poet and ‘producer’ watching a Perseus‐comedy in rehearsal. Taplin (1993) also sees it as a rehearsal, without mask or costume.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Bulle (1937) thinks the performance was a private one for an aristocratic erastes and his young eromenos . Karouzou (1945) takes the absence of a mask to mean that the spectators were a poet and ‘producer’ watching a Perseus‐comedy in rehearsal. Taplin (1993) also sees it as a rehearsal, without mask or costume.…”
Section: Discussionmentioning
confidence: 99%
“…While many scholars, none of whom had actually seen the vase, disputed Caputo's interpretation of its details, none questioned his fundamental assumptions: the first actor shown ‘in the exercise of his profession’ (Karouzou 1945) playing Perseus on the only Attic stage, before the only ancient audience. The identification of the curved object as a curtain was not questioned until 1978, when Hamilton suggested that it might represent a boat.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations